COVID19: Dexamethasone; death or deliverer therefrom? - Robinson, Jared; Banerjee, Indrajit; Annavarapu, Amarendra; Leclézio, Alexandra (Journal of Biomedical Sciences, 2020)
Background: A multitude and wide array of various drugs have been postulated and some even attempted to be used as effective treatments against the virus. The drugs have ranged from antimalarials used in India as a prophylaxis to the disease; namely chloroquine and hydroxychloroquine, to the use of broad-spectrum antiviral drugs such as Remdesivir. Dexamethasone, a cheap, widely available, long acting corticosteroid has been gaining popularity and to some extent fame in the treatment of COVID19 patients. The benefits and use thereof were made apparent after very successful research conducted by the University of Oxford. The Recovery trial, which is one of the world’s largest clinical trials. This trial reported on June 16, 2020 that patients on Dexamethasone at a dosage of 6 mg per day for 10 days have a dramatically reduced mortality particularly in the COVID patients on ventilators. The dexamethasone proved very beneficial in the milder cases of the disease as well and reduced death by 20% in those cases. The proposed mechanism of action by which the dexamethasone drug acts is via impeding the dangerous cytokine storm, an intense immune response that severely renders the lungs damaged. This intense cytokine storm is attributed to the severe complications and respiratory failure noted in COVID19 patients. The long acting dexamethasone would suppress this autoimmune destruction and intense inflammatory reaction, thereby sparing the lungs and the patient’s life. Conclusion: It is therefore of paramount importance that the use of dexamethasone in COVID19 cases is further studied and understood. The benefits of the use of dexamethasone are undeniable and therefore the drug should be implemented into the treatment regime with a guarded approach.